2022
DOI: 10.3390/nano12030336
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Rapamycin Perfluorocarbon Nanoparticles for Preventing Cisplatin-Induced Kidney Injury

Abstract: Cancer treatment-induced toxicities may restrict maximal effective dosing for treatment and cancer survivors’ quality of life. It is critical to develop novel strategies that mitigate treatment-induced toxicity without affecting the efficacy of anti-cancer therapies. Rapamycin is a macrolide with anti-cancer properties, but its clinical application has been hindered, partly by unfavorable bioavailability, pharmacokinetics, and side effects. As a result, significant efforts have been undertaken to develop a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The hydrophobic lipid monolayer of PFC NP could also serve as a carrier for a hydrophobic drug such as rapamycin, which can be stably dispersed and retained in the lipid monolayer of PFC NP. Our previous studies demonstrated that the pharmacokinetics (PK) of rapamycin-loaded PFC NP measured by blood content of rapamycin [ 26 ] agreed with that measured by 19 F MRS [ 76 ], which confirmed the stability of rapamycin PFC NP in circulation required to enable sustained local drug delivery. This current demonstration of therapeutic efficacy for mitigating cisplatin-induced acute kidney injury suggests a new formulation and use for an approved agent, rapamycin, to facilitate chemotherapy in patients requiring cisplatin.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The hydrophobic lipid monolayer of PFC NP could also serve as a carrier for a hydrophobic drug such as rapamycin, which can be stably dispersed and retained in the lipid monolayer of PFC NP. Our previous studies demonstrated that the pharmacokinetics (PK) of rapamycin-loaded PFC NP measured by blood content of rapamycin [ 26 ] agreed with that measured by 19 F MRS [ 76 ], which confirmed the stability of rapamycin PFC NP in circulation required to enable sustained local drug delivery. This current demonstration of therapeutic efficacy for mitigating cisplatin-induced acute kidney injury suggests a new formulation and use for an approved agent, rapamycin, to facilitate chemotherapy in patients requiring cisplatin.…”
Section: Discussionmentioning
confidence: 54%
“…Perfluorocarbon is a safe, effective, and flexible theranostic tool that has been approved for clinical use as a blood substitute [ 67 , 68 ] as well as in angioplasty [ 69 ] and retinal hemorrhage [ 70 ]. Our recently published work also demonstrated the favorable safety profile of rapamycin PFC NP [ 26 ]. PFC NP is composed of a hydrophobic PFC core and surrounding lipid monolayer [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic approaches using conditional knock-out of Atg5 or Atg7 in tubular cells revealed worsened AKI following cisplatin exposure in vivo [ 20 , 37 , 38 ]. Accordingly, the activation of autophagy, e.g., by rapamycin, showed a protective effect against cisplatin-induced renal deterioration [ 39 , 40 ]. Mechanistically, the protective effect of autophagy might be related to its role in mitochondrial renewal since mitochondria are particularly targeted in cisplatin toxicity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%